Health economic evaluation of rehabilitation programmes in the 'Rehabilitation Sciences' Research Funding Programme in Germany. - Krauth C; Hessel F; Klingelhöfer HE; Schweikert B; Hansmeier T; Wasem J (Rehabilitation, 2005)
A main problem of the German rehabilitation sector is to meet the increasing demand for rehabilitation treatment while available resources are scarce. Thus, health economic evaluation is gaining more importance for decision making in the rehab system. In the 'Rehabilitation Sciences' research funding programme the relevance of health economic analyses was recognised from the outset. In nearly all regional networks health economic analyses were conducted - though with different scope. In the first funding period the main focus of health economic evaluation was on (1) patient education programmes and (2) the comparison of inpatient versus outpatient rehabilitation. The projects of the research funding programme have initialised health economic evaluation of rehabilitation in Germany. It was shown that health economics can contribute relevant results for designing rehabilitation concepts. The article concludes with an outlook on the main future questions of rehab economic evaluation.